2022
DOI: 10.21203/rs.3.rs-2155301/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combining skin and olfactory α-synuclein RT-QuIC - towards biomarker-driven phenotyping in synucleinopathies

Abstract: Seeding assays, such as real-time quaking-induced conversion (RT-QuIC), are becoming commonly used in synucleinopathies to detect α-synuclein aggregates. Studies in Parkinson’s disease (PD) and isolated REM-sleep behavior disorder (iRBD) have shown a considerably lower sensitivity in the olfactory epithelium than in CSF or skin. To get an insight into α-synuclein (α-syn) distribution within the nervous system and reasons for low sensitivity, we compared RT-QuIC assessment of nasal brushings and skin biopsies i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…These ndings have been corroborated by independent research groups [39][40][41][42][43]. Motivated by these discoveries, we have expanded our inquiry to encompass the most prevalent neurodegenerative condition, AD, and other tauopathies.…”
Section: Discussionmentioning
confidence: 65%
“…These ndings have been corroborated by independent research groups [39][40][41][42][43]. Motivated by these discoveries, we have expanded our inquiry to encompass the most prevalent neurodegenerative condition, AD, and other tauopathies.…”
Section: Discussionmentioning
confidence: 65%
“…The detected biofluids and peripheral tissues included CSF, skin, OM, saliva, GI tract, and NEs from plasma, serum and SMG. The characteristics of these studies are described in Table 1 [7–14, 16–49, 65]. The PRISMA flowchart is displayed in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, CSF α‐syn SAAs displayed high sensitivity (84%–100%) and specificity (82.3%–100%) in the diagnosis of PD and other synucleinopathies [7–31]. With the advancement in detecting pathological α‐syn in biofluid, subsequent studies applied SAAs to detect α‐syn in various specimens such as skin (sensitivity 75%–100%; specificity 83%–100%) [11, 32–36], OM (sensitivity 46%–69%; specificity 90%–91%) [37–41], GI tract (sensitivity 10%–83%; specificity 75%–100%) [42–44], saliva (sensitivity 76%–84%; specificity 78%–94%) [45, 46], submandibular gland (SMG) (sensitivity 95%; specificity 100%) [26, 47], serum (sensitivity 94.6%; specificity 92.1%) [48] and neuron‐derived extracellular vesicles (NEs) from plasma (sensitivity 100%; specificity 100%) [49]. To date, some meta‐analyses have calculated the diagnostic efficacy of SAAs for PD, Lewy body dementia (DLB), multiple system atrophy (MSA) and prodromal α‐synucleinopathies.…”
Section: Introductionmentioning
confidence: 99%
“…Influenza [5] and hospitalization due COVID-19 infection [31] have previously been identified as potential risk factors for PD. A recent study comparing α-synuclein seed amplification assays (SAA) of nasal brushings and skin biopsies found that the distribution of α-synuclein deposition is not uniform across PD patients [32]. The study supported a hypothesis based on two subtypes of PD: “body-first,” where pathogenic α-synuclein starts aggregation in the enteric nervous system and spreads to the brain, and “brain-first,” where it begins in the brain and then affects the rest of the body [33].…”
Section: Discussionmentioning
confidence: 99%